UBUmaterial: building a performative archive on Instagram. Issue 1 (2nd January 2022) - Angelopoulos, Tasos; Konstantinakou, Panayiota; Papagiannouli, Christina
ABSTRACT: This document records and reflects on the process of building an innovative format, a performative archive on Instagram, the UBUmaterial, by Papalangki theatre company (Greece). It exhibits the occasion of its emergence, discusses the process of its development and presents the tools used and the materials produced as part of it. Furthermore, it gives information on its impact and considers its afterlife. UBUmaterial unfolds as a performative archive that occupies not a physical stage but a 'cyberstage' (Instagram) and is dedicated to the exhibition of Papalangki's attempt to rehearse Alfred Jarry's Ubu Roi at home, as a result of the restrictions of the COVID-19 pandemic. Nevertheless, traditional rehearsal techniques and theatre approaches were not adopted, since it appeared necessary for all dramatic elements of the original play (language, character, plot) as well as the acting style to be adjusted to the new digital environment. Extensive use of digital tools and Instagram features enabled a rich output of video production. The album-like format of Instagram allowed for the creation of a virtual modelbook (in Brechtian terms), where videos from rehearsals were posted in a non-linear order. The archive will remain accessible forever and hopefully form a basis for new excursions.